Self-Healing Behavior of Hydrothermally Engineered HAp/PAA Coatings on Magnesium Alloy WE43 - Erryani, Aprilia; Rokhmanto, Fendy; Setyawan, Albertus Deny Heri; Thaha, Yudi Nugraha; Zakiyuddin, Ahmad; Kartika, Ika; Harjanto, Sri (National Research and Innovation Agency (BRIN), 2024)
This work examines the self-healing properties and corrosion prevention mechanisms of hydrothermally synthesized HAp/PAA (hydroxyapatite/polyacrylic acid) composite coatings on magnesium alloy WE43. The coatings were produced with different PAA concentrations (0.15, 0.3, and 0.5 wt.%) by a hydrothermal method at 140 °C for 3 hours. The composite layers were analyzed using FTIR (fourier transform infrared spectroscopy), SEM (scanning electron microscopy), and EIS (electrochemical impedance spectroscopy) to assess their structural and electrochemical properties, as well as their self-healing capabilities via a scratch–immersion test in Hank’s solution at 37 °C for 48 hours. FTIR analysis confirmed the simultaneous presence of HAp and PAA phases without any chemical reaction, indicating physical contact through hydrogen bonding. The elevation of PAA concentration markedly affected coating morphology, resulting in denser and more uniform structures characterized by spherical HAp crystals at 0.5 wt.% PAA. SEM analysis following scratching and immersion demonstrated that the 0.5 wt.% PAA coating successfully preserved surface integrity and displayed partial restoration of the injured region via the reprecipitation of Ca–P compounds. The EIS findings indicated that the 0.5 wt.% PAA coating maintained the maximum impedance modulus (>10⁴ Ω·cm²) and a steady phase angle after 48 hours of immersion, therefore affirming its exceptional corrosion resistance and self-healing properties. The results demonstrate that an ideal PAA content fosters a dense, ion-responsive hybrid layer that effectively reinstates barrier characteristics following mechanical impairment. The hydrothermally produced 0.5 wt.% HAp/PAA coating offers an efficient self-healing and corrosion-resistant surface for WE43 magnesium alloy, indicating significant potential for use in next-generation biodegradable implant systems.